Advice-seeking and advice-giving strategies of Malaysian women in an online support forum for IVF / Pung Wun Chiew - Pung , Wun Chiew (2017)
Despite the increasing prominence of the Internet for a variety of social purposes, research on how advice is sought and given online is still lacking, especially in context where the strategies are tied to communities of a certain culture and gender. This study aimed to investigate the advice-seeking strategies, the advice-giving strategies, and the influence of culture when advice is solicited and given online among women in a Malaysian online forum on in-vitro fertilization (IVF). Six months of IVF-related messages posted in a local online forum were analyzed, in which 251 were adviceseeking messages, and 369 were advice-giving messages. The analysis took on a largely qualitative approach with some quantitative aspect of counting, incorporating Locher’s (2006) system of coding messages, Kouper's (2010) typology of advice-seeking and advice-giving patterns, Ruble's (2011) message-content analysis method, and Goldsmith's (2004) model of advice. The findings revealed question-asking as the most frequently utilized strategy of seeking advice, followed by problem-description, and lastly, the least used advice-seeking strategy was to request for it explicitly. However, offering or giving advice directly ranked top as the most preferred advice-giving strategy. This was followed by the advice-giving strategies of describing one's own experiences, giving indirect advice, providing general information, referring the message-recipient to another advice source, and narrating other people's experiences. It was also found that the content of the advice-seeking messages was mostly specific to the advice-seeker's problem, with many instances of mitigation and expressions of the advice-seeker's distress. On the other hand, the advice-giving messages showed the advice-givers' tendency to bond with the advice-recipients besides the use of hedging devices to downtone the advice's impositional level. Interaction in the online forum was also governed by the fact that the communication medium was computer-mediated communication (CMC), and the presumption that the forum members were Malaysian women, and subsequently, the topic under discussion was culturally taboo. Thus, although there was freer self-expression by the participants, the manner in which they interacted still showed their interests to form close relationships, and in ways that were culturally appropriate. As such, despite the anonymity afforded by CMC, several aspects of the interaction still showed cultural influence at both message-content and discourse levels.